Work Culture Revolution in Human Resource Management in the Era of Remote Work Flexibility and Global Collaboration - Wulandari, Nuning Yayuk (International Journal of Education, Management, and Technology, 2025)
The work culture revolution has become one of the most profound phenomena in the development of human resource management (HR) in the modern era. One of the biggest impacts of this change is the emergence of remote work flexibility and global collaboration, which is further changing the dynamics of the workplace. The purpose of this study is to analyze the impact of the work culture revolution on human resource management (HR) in the era of remote work flexibility and global collaboration. This study uses a descriptive qualitative approach to analyze the work culture revolution in human resource management (HR) in the era of remote work flexibility and global collaboration. The results of this study show that the work culture revolution that includes remote work flexibility and global collaboration has brought significant changes in human resource (HR) management. Work flexibility has been shown to improve employees' well-being and job satisfaction, giving them more control over the balance of their personal and professional lives. However, the main challenge that arises is how companies can manage the performance of employees who work remotely, especially in terms of performance measurement, productivity monitoring, and ensuring effective communication within teams spread across multiple locations and time zones. Large companies, which are more accustomed to adopting advanced technology, are more successful in addressing these challenges compared to smaller companies, which still rely on a physical presence-based approach. Data from this study reinforces those findings in terms of performance management systems, 78% of large companies have switched to results-based systems, while 55% of small companies still rely on physical presence to monitor employee performance. In addition, platforms such as Zoom (78%) and Microsoft Teams (65%) dominate the use for remote collaboration, indicating that technology plays an important role in facilitating communication across locations and time zones. On the other hand, companies that pay more attention to the mental well-being of employees, by providing online counseling services and wellness programs, tend to have higher engagement rates. This can be seen from 60% of companies that provide mental health support to their employees.